Efficacy and safety evaluations of adalimumab biosimilars in the treatment of psoriasis - Changkun Li; Yixuan Sunhe; Hui Zhou; Weihua Dong (Taylor & Francis Group, 2023)
Purpose We aimed to systematically evaluate the efficacy and safety of adalimumab biosimilar agents in the treatment of moderate-to-severe plaque psoriasis, in order to provide evidence-based reference data for clinical medicine. Materials and Methods Five databases were searched by electronic retrieval: PubMed, Embase, Cochrane Library, WanFang and CNKI (China National Knowledge Internet). The retrieval period was from the establishment of each database up to April 2022. Randomized controlled trials (RCTs) on adalimumab biosimilar agents compared with their reference agents in the treatment of moderate-to-serve plague psoriasis were included. A meta-analysis using RevMan software was applied to 8 RCTs involving 2589 patients. Results After 16 weeks of medication, there was no significant difference in the response rates of adalimumab biosimilar agents and their reference agents defined as a decrease in the Psoriasis Area and Severity Index (PASI) of ≥75% (PASI 75) (p > 0.05), or in the PASI 50, PASI 90 and PASI 100 measures (p > 0.05). After 16 weeks and 24 weeks of medication, there was no significant difference in the incidence rate of serious adverse events (SAEs) between adalimumab biosimilar agents and their reference agents (p > 0.05). After 16 weeks, 24 weeks and 51 weeks of medication, there was no significant difference in withdrawal rate due to SAEs, treatment-emergent adverse events and adverse events of special interest between adalimumab biosimilar agents and their reference agents (p > 0.05). Conclusion These findings suggest that biosimilar agents of adalimumab have an overall efficacy and safety profile for psoriasis comparable to those of their reference agents.